The theater of war what ancient Greek tragedies can teach us today - Doerries, Bryan (Alfred A. Knopf, 2015)
For years, theater director Bryan Doerries has led an innovative public health project that produces ancient tragedies for current and returned soldiers, addicts, tornado and hurricane survivors, and a wide range of other at-risk people in society. Drawing on these extraordinary firsthand experiences, Doerries clearly and powerfully illustrates the redemptive and therapeutic potential of this classical, timeless art: how, for example, Ajax can help soldiers and their loved ones better understand and grapple with PTSD, or how Prometheus Bound provides new insights into the modern penal system."--Jacket flap